Framing dalam Pemberitaan Krisis: Studi Pada Pemberitaan Krisis Permendikbudristek No.30 Tahun 2021 - Rona Rizkhy Bunga Chasana (Mediator: Jurnal Komunikasi, 2023)
The release of the Minister of Education and Culture Regulation on the Prevention and Handling of Sexual Violence (Permendikbudristek PPKS) No. 30 of 2021 is expected by the government to overcome the problem of sexual violence that occurs on campus. But apparently, this regulation has caused cons from various parties who disagree with the phrase "without the victim's consent" which is contained in several articles. Public opinion ensued on social media and news related to the pros and cons appeared in various online media. Media coverage of crisis issues can exacerbate the crisis that occurs in an organization. The crisis research related to Permendikbudristek PPKS was chosen to see how media framed the crisis. A total of 35 articles from Republika.co.id and Kompas.com were analyzed. Using quantitative content analysis, this study was carried out by exploring 5 media frames that usually appear in news related to crisis: attribution of responsibility, conflict, economic consequences, morality, and human interest. The result is conflict are the most dominant frames followed by responsibility frames. Meanwhile, morality and human interest are the least used frames. Crisis frames are important for PR practitioners to understand media coverage during a crisis and provide the right response to reduce its impact.